Sexing the history of Indian anti-colonial internationalism: White women, Indian men and the politics of the personal - Simonow, Joanna (Gender & history, 2024)
In contrast to the wealth of literature on the gendered and sexual politics of Indian nationalism, studies on the internationalisation of Indian anti-colonial nationalism are rarely informed by the twin themes of gender and sexuality. As Indian activists traversed international political spaces in the early twentieth century, they frequently entered into sexual relations with white women. This article explores the possible political consequences of such sexual contact through a study of the personal lives of Arathil Candeth Narayanan Nambiar and Manabendra Nath Roy and their relationships with the largely unknown German-born sisters, Eva and Lu Geissler.